ANALISIS PENENTUAN BIAYA PELAYANAN PASIEN RAWAT INAP PADA PUSKESMAS PALENGAAN PAMEKASAN - Zakhra, Aminatus; Khusairi, Khusairi (Fakultas Ekonomi, Program Studi Akuntansi, 2019)
This study aims to determine the cost of inpatient services at Palengaan Pamekasan Community Health Center. The data analysis method used in this study uses descriptive quantitative analysis. Based on the results of the study indicate that the determination of the cost of inpatient service using the Activity Based Costing method for VIP class inpatient services costs Rp. 160,230.36, - the current tariff is Rp. 150,000, - including the difference of Rp. 10,230.36, - and in Zaal's class Rp. 92,868.85, - registration of the current tariff of Rp. 75,000, - including the difference of Rp. 17,868.85, - and the conclusions in using the Activity Based Costing method show that the results are higher than the current rates.